2018
DOI: 10.2147/dddt.s170816
|View full text |Cite
|
Sign up to set email alerts
|

Sintered dicalcium pyrophosphate treatment attenuates estrogen deficiency-associated disc degeneration in ovariectomized rats

Abstract: BackgroundEstrogen deficiency is associated with musculoskeletal disorders. Sintered dicalcium pyrophosphate (SDCP) is a novel antiosteoporotic agent. In this study, we examined its use for restoration of bone quality and attenuation of disc degeneration in ovariectomy rats.MethodsSixty female Sprague Dawley rats were randomly divided into 3 groups, namely sham group undergoing sham surgery, ovariectomy (OVX) group receiving an equivalent volume of isotonic sodium chloride solution, and OVX/SDCP group orally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Osteoporosis is characterized by reduced bone mass, bone microstructure destruction, and high fracture risk, which is more common in postmenopausal women. Some studies have confirmed that osteoporosis caused by estrogen deficiency can accelerate IVDD [ 20 , 21 ]. For the simulation of this population, we performed OVX surgery to create a model of ASDD with osteoporosis in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is characterized by reduced bone mass, bone microstructure destruction, and high fracture risk, which is more common in postmenopausal women. Some studies have confirmed that osteoporosis caused by estrogen deficiency can accelerate IVDD [ 20 , 21 ]. For the simulation of this population, we performed OVX surgery to create a model of ASDD with osteoporosis in rats.…”
Section: Discussionmentioning
confidence: 99%